2020
DOI: 10.1128/aem.00165-20
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Abundance and Diversity of Phototrophs in Mats from Morphologically Variable Microbialites in Great Salt Lake, Utah

Abstract: Microbial mat communities are associated with extensive (∼700 km2) and morphologically variable carbonate structures, termed microbialites, in the hypersaline Great Salt Lake (GSL), Utah. However, whether the composition of GSL mat communities covaries with microbialite morphology and lake environment is unknown. Moreover, the potential adaptations that allow the establishment of these extensive mat communities at high salinity (14% to 17% total salts) are poorly understood. To address these questions, microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 83 publications
3
12
0
1
Order By: Relevance
“…The The community composition of control samples from a microbialite with a healthy periphyton was largely consistent with compositions found at other times and locations [6,16],…”
Section: Results In 2022supporting
confidence: 79%
“…The The community composition of control samples from a microbialite with a healthy periphyton was largely consistent with compositions found at other times and locations [6,16],…”
Section: Results In 2022supporting
confidence: 79%
“…However, the incorporation of molecular work such as ribosomal RNA (rRNA) gene sequencing and functional genomics to studies on hypersaline biota may help challenge this norm and refine ecological modelling. For example, in Great Salt Lake, the ‘architects’ of microbialite structures have been discerned, namely photosynthetic cyanobacteria and diatoms (Lindsay et al ., 2017, 2019; Kanik et al ., 2020), which echoes that of the Shark Bay stromatolites in Australia (Edgcomb et al ., 2014; Ruvindy et al ., 2016). However, an exploration of the total microbial communities in Great Salt Lake mats, using both 16S rRNA gene sequencing and metagenomic sequencing, revealed that the dominant organisms are in fact secondary producers, aerobic heterotrophic bacteria that supplement their energy metabolism using light energy via light‐harvesting rhodopsin pigments and other photosynthetic reaction centres (Kanik et al ., 2020).…”
Section: Future Research Avenuessupporting
confidence: 72%
“…Research related to the lake has primarily focused on the human environment, salt tolerant plants, and salt production, yet there are few reports on the microbial diversity and biological mechanisms of salt tolerance in this area ( Huan et al, 2019 ; Ming et al, 2020 ; Gao et al, 2021 ). At the same time, biogeochemical properties affect the composition and distribution of special halophilic and salt-tolerant microbial communities in this area ( Kanik et al, 2020 ). In view of the special nature of the saline environment of Yuncheng Salt Lake, the high-salt soil and the salt lake itself provide excellent opportunities for research on the isolation and screening of salt-tolerant microorganisms and exploring mechanisms of biological salt tolerance.…”
Section: Introductionmentioning
confidence: 99%